ФУНКЦИОНИРОВАНИЕ СОЦИАЛЬНО МАРКИРОВАННЫХ ГЛАГОЛОВ В РУССКОМ ЯЗЫКЕ (Filološke studije, 2019)
The socially marked verbs which describe relations of communicants in a dialogue are considered in the article. The facts that dictionary definitions do not con- sider the social marking of а verb and value of a verb depends on a number of factors is shown оn a material of the National corps of Russian. These facts are the lexical and grammatical polysemy of verb, the concrete form of verb, the real and psychological position of speaker and the general context of the verb use. Functioning of verbs in speech shows that their semantic potential in sense of describing the communication situations is considerable above than it is presented in dictionaries.